Epidemiology of infertility in the district of Colombo, Sri Lanka. - Samarakoon, S (My University, 1994)
The objectives of the study were to assess the point prevalence of primary and secondary infertility,identify risk factors associated with primary infertility and describe causes of primary infertility in the district of colombo.The study consisted of two phases.A community based cross sectional prevalence study and a cas control study.The finding suggest that prevention of post partum sepsis and post abortal sepsis would be an important factor in preventing secondary infertility.Although the prevalence of primary infertility can be considered low in comparison to other reproductive failures,in planning services the relative importance of the problems and the cost effectiveness of the treatment should be considered.Wide speard coverage of basic investigations and a center of excellence where advanced techniques for the diagnosis of infertility are available should be established